Pengaruh Work Life Balance terhadap Kinerja Karyawan melalui Komitmen Organisasi pada Karyawan PT. Bhinneka Life Indonesia Cabang Surabaya - Ardiansyah, Choirul Adam; Surjanti, Jun (Jurnal Ilmu Manajemen, 2020)
The purpose of this study is to analyze the relationship between work-life balance and employee performance through an organizational commitment to the employees of PT. Bhinneka Life Indonesia Surabaya branch. This type of research is quantitative research. The study used a saturated sample technique with a total of 50 permanent employees at PT. Bhinneka Life Indonesia Surabaya branch. From the results of statistical analysis, this study uses Partial Least Square (PLS) and is assisted with smartPLS 3.0 software. This research shows the results of work-life balance has no relationship with employee performance. Work-life balance has a positive effect on commitment. While commitment has a relationship with performance. And the commitment variables can mediate the effect between work-life balance on employee performance. This study shows the results of work-life balance have a smaller direct relationship than an indirect effect on the performance of employee. The implications are based on results of research applied to companies that superiors can provide training to employees on the importance of managing the time between life at work and life outside of work such as life at home. Also, the employees can pay attention to their comfort while working or in receiving bonuses when the targets set by the company have been achieved. Supervisors can also provide other training to the employees to improve the quality of their work.